Influencing collective land tenure indicators. Burkina Faso, Kenya and Sudan case studies - Flintan, Fiona E; Nassef, Magda; Sulieman, Hussein; Otieno, Ken; Sawadogo, I.; Langdown, Ian; Locke, A. (Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises, 2025)
The objectives of the study were to better comprehend pastoral collective (communal) tenure, explicitly focusing on perceived tenure security, and developing characteristics and indicators for measuring it. Two layers of tenure and tenure security were considered: that of the group and that of individuals within the group, recognizing that groups are not homogeneous.